Loss of circulating CD27+ memory B cells and CCR4+ T cells occurring in association with elevated EBV loads in XLP patients surviving primary EBV infection - Malbrán, Alejandro (2004)
Detailed longitudinal studies of patients with X-linked lymphoproliferative disease (XLP) may increase our understanding of the immunologic defects that contribute to the development of lymphoma and hypogammaglobulinemia in XLP. We describe progressive changes observed in immunoglobulin concentrations, lymphocyte subsets, and Epstein-Barr virus (EBV) loads occurring in a 2-year period in a newly infected, but otherwise healthy, carrier (patient 9). We compare these findings with those observed in the patient's brother, who had hypogammaglobulinemia and XLP (patient 4). Immunoglobulin G (IgG), IgM, and IgA concentrations increased in patient 9 during acute EBV infection, but thereafter they decreased steadily to concentrations consistent with hypogammaglobulinemia, reaching a plateau 5 months after infection. In both patients, CD19+ B-lymphocyte rates remained lower than 3%, with a contraction of the B-cell memory compartment (CD27+ CD19+/CD19+) to 20% (normal range, 32%-56%). T-lymphocyte subpopulations showed a reduction in CD4+ T-cell counts and a permanent CD8+ T-cell expansion. Interestingly, CXCR3 memory TH1 cells were expanded and CCR4+ T H2 lymphocytes were reduced, suggesting that abnormal skewing of memory T-cell subsets might contribute to reduced antibody synthesis. Despite an expanded number of CD3+CD8+ lymphocytes, increased EBV loads occurred in both patients without overt clinical symptoms of mononucleosis, lymphoproliferative disease, or lymphoma.